Image as Agency: A Conceptual Model with Ontological Import for Human and Divine Persons - Kelly, Jon (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2025)
This essay argues for a dual-aspect, substantival and functional, model of the image of God following the relation of image to agency and to Christ as the exemplar human agent developed in two parts from exegesis to metaphysics. In part 1, I define agency and trace the functional aspect of the relation of image to agency through the arc of Scripture from the creation narrative to its fulfillment in Christ and Christian regeneration. In part 2, I define image metaphysically and highlight an inference of identity Jesus makes between himself and the Father founded upon their agencies; Jesus’ identity includes the image of God grounded in the divine person of the Son. I argue that Jesus’ inference extends the concept of image as agency to include an ontological entailment such that the agent is identical with an immaterial “person.” The model provides reason to think that agency is the fundamental operator of God’s image throughout Scripture and that divine and human “persons” are immaterial substances, powerful and responsible agents.